2010
DOI: 10.3354/dao02219
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced marine flexibacteriosis in Atlantic salmon smolts Salmo salar. I. Pathogenicity

Abstract: Tenacibaculum maritimum causes marine flexibacteriosis in many cultured fish species, including Atlantic salmon Salmo salar in Tasmania, Australia. Several aspects of the pathogenicity of this bacterium were investigated in naive Atlantic salmon smolts using different isolates, growth conditions and doses to produce a model of infection. We found that T. maritimum is pathogenic to Atlantic salmon using either marine Shieh's or marine Ordal's culture medium. The use of aeration in broth culture produced a dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(37 reference statements)
4
9
0
Order By: Relevance
“…Unlike other skin conditions that occur with a high number of ulcers distributed anywhere on the body surface (Wiklund & Bylund 1993;Roberts 2001;Austin & Austin 2007;Bruno et al 2007;Kodama, Denso & Nakagawa 2007), in the present study, no more than 2-3 severe ulcerative lesions, mainly located in the fins, were observed in the same fish. Other gross pathological findings previously recorded (Carson, McCosh & Schmidtke 1992;Handlinger et al 1997;van Gelderen et al 2011) in Atlantic salmon naturally or experimentally infected with T. mari- timum, such as erosion of the oral cavity and jaws, eye damage or gill necrosis, were not observed in the current study, even in severely affected sole. These findings are consistent with the chronic form of the disease described in Atlantic salmon by van Gelderen et al (2011) using a dose-dependent infectious trial.…”
Section: Santos 2002; Van Gelderen Carson and Nowak 2011)supporting
confidence: 55%
“…Unlike other skin conditions that occur with a high number of ulcers distributed anywhere on the body surface (Wiklund & Bylund 1993;Roberts 2001;Austin & Austin 2007;Bruno et al 2007;Kodama, Denso & Nakagawa 2007), in the present study, no more than 2-3 severe ulcerative lesions, mainly located in the fins, were observed in the same fish. Other gross pathological findings previously recorded (Carson, McCosh & Schmidtke 1992;Handlinger et al 1997;van Gelderen et al 2011) in Atlantic salmon naturally or experimentally infected with T. mari- timum, such as erosion of the oral cavity and jaws, eye damage or gill necrosis, were not observed in the current study, even in severely affected sole. These findings are consistent with the chronic form of the disease described in Atlantic salmon by van Gelderen et al (2011) using a dose-dependent infectious trial.…”
Section: Santos 2002; Van Gelderen Carson and Nowak 2011)supporting
confidence: 55%
“…The temperature of 12°C used in all the experiments is much lower than previously performed challenge studies involving T. maritimum . This is particularly relevant when comparing to other experiments previously performed with Atlantic salmon smolts, where temperatures up to 20°C were used (Handlinger et al., ; Soltani et al., ; van Gelderen et al., , ). These higher temperatures are at the upper range of optimal rearing conditions for Atlantic salmon smolts, which may have had an influence on results (Jonsson, Forseth, Jensen, & Næsje, ).…”
Section: Discussionmentioning
confidence: 98%
“…In Tasmania, Australia, T. maritimum has been linked to tenacibaculosis in Atlantic salmon smolts. This disease has been reproduced in the laboratory by bath infecting fish for a short period of time (1 hr) at a high concentration (Handlinger et al., ; Soltani, Shanker, & Munday, ; Soltani et al., ; van Gelderen et al., ; van Gelderen, Carson, & Nowak, ). These experiments also showed that Atlantic salmon was more susceptible than rainbow trout ( Oncorhynchus mykiss , Walbaum) and that exposure at lower salinities (15 ppt) gave very low mortality (Handlinger et al., ; Soltani et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using the phenotypic markers described, the isolates were grouped and ranked in order to make selections for later pathogenicity and vaccination trials (van Gelderen et al. 2009, in press).…”
Section: Discussionmentioning
confidence: 99%